Values and their importance in the curriculum Numbers - Mouloud Tawfiq, Bashaer (Al-Adab Journal, 2019)
The objective of the current research was to identify the values ​​and their importance in the curriculum. The limits of the search for information and literature that contribute to achieve its objectives were followed by the researcher to study the descriptive analytical method of its importance in the curriculum as the concept of values ​​and their characteristics, , Values ​​and family formation values ​​and political formation, and educational mechanisms to integrate values ​​in the curriculum, the research has reached some conclusions such as: 1-The importance of values ​​in the life of society, the role it plays in the integration of social structure and the harmony of the members of society and their cohesion in the face of the challenge of fate in a world where the position of the unified community of great importance for its survival and sustainability. . 2-The educational values ​​of a nation of nations are closely linked to their culture. Therefore, separating Islamic educational values ​​from their proper cultural framework and integrating them into a climate of cultural duplication or leaving them under the threat of cultural invasion presents them with solubility. And made a sound civilized reality. Proposals 1.Studying the values ​​in the modern curriculum in different educational stages 2. Comparison of modern curricula in neighboring countries.